2022
DOI: 10.1093/oso/9780197603512.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

What Happened to the Vital Center?

Abstract: How did a country once praised or blamed for its pragmatism came to be so sharply divided? What Happened to the Vital Center? demonstrates that American politics has become so rancorous because it has been unable to heal wounds opened up by 1960s-era protest and institutional change. As various chapters document, this tumultuous decade resulted in the joining of presidential power, social activism, and high stakes battles over domestic and foreign policy. Surveying the course of American history, the book furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Finally, while recent work has shown that increasing reliance on out-of-district fundraising makes U.S. House members more responsive to national donor base (Canes-Wrone & Miller, 2022), we find similar patterns of behavior for Senate behavior, even though Senators are theoretically less susceptible to the influence of party organizations in government (Smith et al, 2013). We conclude that this finding is of special relevance to ongoing work on political nationalization, given the Senate's institutional grounding in territorially grouped constituencies, and the challenge partisan polarization poses to constitutional federalism (Jacobs and Milkis, 2022).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Finally, while recent work has shown that increasing reliance on out-of-district fundraising makes U.S. House members more responsive to national donor base (Canes-Wrone & Miller, 2022), we find similar patterns of behavior for Senate behavior, even though Senators are theoretically less susceptible to the influence of party organizations in government (Smith et al, 2013). We conclude that this finding is of special relevance to ongoing work on political nationalization, given the Senate's institutional grounding in territorially grouped constituencies, and the challenge partisan polarization poses to constitutional federalism (Jacobs and Milkis, 2022).…”
Section: Introductionsupporting
confidence: 52%
“…As such, it remains an open question as to what should be done, since any corrective will make a normative claim on which constituency is most important: a national, potentially more ideologically unrepresentative one, or many parochial ones, that may be less ideologically-driven, but less representative of the nation, as a whole. It is constitutionally ambiguous what steps Congress could take, or even whether the parties themselves could set a regulation on individual candidates' receipts, if they chose to run under the party banner (Cutler, 1986); restricting out-of-state receipts would alter donors' incentives, perhaps increasing the appeal of donating to party organizations over individual candidates, limiting the direct influence of out-of-state donors, and enhancing collective party responsibility (Jacobs and Milkis, 2022). Alternatively, in an era of rising campaign costs and increasing competition, no partisan is likely to desire further constraints to the supply of campaign funds they could have at their disposal.…”
Section: Discussionmentioning
confidence: 99%
“…Reagan thus bestowed bipartisan legitimacy on the merging of executive prerogative and partisanship, which culminated with the ascension of Donald Trump to the White House (Jacobs and Milkis 2022, Chapter 6). The maturing of executive‐centered partisanship has not made presidents all powerful.…”
Section: Discussionmentioning
confidence: 99%
“…Through the late spring and into the summer, the Trump administration advocated stricter curbs on voting, persisted in its efforts to undermine the Affordable Care Act and other social welfare programs, and intensified its efforts to redefine education policy, all under the guise of battling the coronavirus, albeit not in the way public health officials and Democratic governors and mayors wanted. 67 No actions more fully reveal the power seized by the administration under the cover of the pandemic than its crackdown on immigration into the United States, including through legal pathways.…”
Section: Donald Trump and Covid-19mentioning
confidence: 99%